Sediment in sungai Sarawak : post-barrage - Chai, Su Boon (Universiti Malaysia Sarawak, (UNIMAS), 2006)
The general objective of this ~tudy was to reVIew the findings of the sedimentation study that was conducted as part of the Sungai Sarawak Environmental Control and River Management Study, 1997. One of the crucial problems related to the performance of reservoirs such as the Sungai Sarawak Barrage impoundment is the progressive reduction in storage capacity due to sedimentation. Reservoir sedimentation raises flood plain levels reducing its effectiveness for flood mitigation purposes. The primary study area was the river section beginning from Henderson Point (near Ban Hock Wharf) to the Sungai Sarawak Barrage further downstream. Channel cross-section and longitudinal profiles were generated through manual profiling using navigation charts. Subsequently, comparative analyses of the profiling results were done using traditional methods. Comparisons between actual and simulated levels were conducted. The effectiveness of barrage operation from a sediment re-suspension aspect was roughly gauged by comparing turbidity measurements taken prior to and during barrage gate operation. The assessment ofcross sectional profiles conducted in this study suggests that most sections of the river reach in question were deeper and wider. This indicates that the river reach from Henderson Point to Sungai Sarawak Barrage has not been affected by impoundment sedimentation in any detrimental manner. The increase in total suspended solids level during gate operation as opposed to levels prior to operation was quite appreciable. It is reasonable to assume that the turbulence created during gate operations is sufficient to re-suspend some of the settled sediment particles and effectively transport the pa:rticles out of the impoundment. Generally, the impoundment sedimentation upstream of the Sungai Sarawak is not significant due to regmar gate operation.